Optimal oral antithrombotic regimes for patients with acute coronary syndrome: a network meta-analysis. - Yicong Ye (PLoS ONE, 2014)
We performed a network meta-analysis to investigate the optimal antithrombotic regime by indirectly comparing new antithrombotic regimes (new P2Y12 inhibitors plus aspirin or novel oral anticoagulants on top of traditional dual antiplatelet therapy [DAPT]) in patients with acute coronary syndrome (ACS).A systematic search of MEDLINE, EMBASE, and the Cochrane databases was performed to identify all phase 3 randomized controlled trials (RCTs) involving novel oral anticoagulants or oral P2Y12 inhibitors in patients with ACS. Major adverse cardiac events (MACE) were regarded as the efficacy endpoint, and thrombolysis in myocardial infarction (TIMI) major bleeding events were used as the safety endpoint. The net clinical benefit was calculated as the sum of MACE and TIMI major bleeding events.Five phase 3 RCTs with 64,476 ACS patients were included. Although there were no significant differences among new antithrombotic regimes, rivaroxaban 5 mg twice daily plus traditional DAPT might be the most effective in reducing the incidence of MACE, accompanying the highest risk of TIMI major bleeding. Ticagrelor plus aspirin presented slight advantage on the net clinical benefit over other new antithrombotic regimes, with the highest probability of being the best regimes for net clinical benefit (35.0%), followed by prasugrel plus aspirin (28.0%), and rivaroxaban 2.5 mg twice daily plus traditional DAPT (19.5%).Novel antithrombotic regime with ticagrelor plus aspirin brings a larger clinical benefit in comparison with other regimes, suggesting that it may be the optimal antithrombotic regime for patients with ACS.